Guaiacol oxidation: theoretical insight into thermochemistry of radical processes involving methoxy group demethylation. (2nd December 2022) - Biela, Monika; Kleinová, Andrea; Klein, Erik
Abstract: Guaiacol (2-methoxyphenol) is naturally occurring phenolic compound essential in various research areas. Oxidative transformation of guaiacol can lead to the formation of various products, including 1, 3-benzodioxole or ortho -quinone. Therefore, this study is focused on the investigation of the reaction enthalpies of experimentally observed guaiacol oxidation pathways in gas-phase, as well as in non-polar environment and aqueous solution. Corresponding Density Functional Theory (DFT) calculations were carried out using two hybrid functionals (M06-2X and B3LYP-D3). All reaction enthalpies, as well as Gibbs free energies, were also calculated using composite ab initio G4 method. M06-2X and G4 results show mutual agreement and the best accordance with available experimentally determined reaction enthalpies. Obtained Gibbs free reaction energies indicate that formation of ortho -quinone is thermodynamically preferred to formation of 1, 3-benzodioxole at 298 K in studied environments. Moreover, all computational methods confirm that the reaction enthalpy of methoxy group demethylation, i.e. O–C bond dissociation enthalpy (BDE), is substantially lower in comparison to the enthalpy of hydrogen atom transfer from phenolic OH group. In the case of phenoxide anion of guaiacol, which can be formed in ionization supporting solvents, O–C BDE shows further significant decrease, exceeding 50 kJ mol −1, in comparison to parent molecule. HIGHLIGHTS: Reaction enthalpies and Gibbs free energies of individual steps of guaiacol transformation to 1, 3-benzodioxole or ortho- quinone are studied in three environments. M06-2X functional and composite ab initio G4 methods provide reliable O–H and O–C bond dissociation enthalpies. Dissociation enthalpy of methoxy group O–C bond is lower by ca. 100 kJ mol −1 in comparison to phenolic O–H bond. Phenoxide anion of guaiacol shows substantially lower O–C BDE than parent molecule.